Peningkatan Masyarakat Domas Melalui Inovasi Produk Olahan Ikan Payus dan Optimalisasi Pemasaran Digital di Era Ekonomi Kreatif [Empowering the Domas Community Through Innovation in Processed Payus Fish Products and Optimization of Digital Marketing in the Creative Economy Era] - Syifa Fajar Maulani; Wafa Nurul Hakim; Azwin Jahid Al Farizhi; Shoimah Annisa Ramadhani; Muhammad Rizky; Siti Kurotul Ainiah; Faishal Sauqi Ramadhani (Indonesia Berdaya, 2026)
The coastal region of Banten Province possesses significant potential in the fisheries sector, particularly in Domas Village, Serang District, known for its Payus fish production. However, limited innovation in processing catches has resulted in low market value for the fish, while many fishing families rely entirely on unpredictable ocean yields due to weather factors. In response to this situation, students from the Marine Logistics Student Association (HIMALOKA) at the Indonesian Education University conducted community service activities aimed at enhancing entrepreneurial skills and economic independence among fishermen's wives. Through training on processing Payus fish into Crispy Bontot (CRISBON) products, participants were introduced to product innovation processes, attractive packaging techniques, and digital marketing strategies to expand market reach. This initiative employed a Participatory Action Research (PAR) approach, actively involving the community from planning to evaluation stages. The results indicated an improvement in participants' skills in entrepreneurship, product innovation, packaging, and digital marketing, with the highest increase observed in digital marketing skills at 12.18%, demonstrating that participants began to leverage technology as a means of promotion and business development. Overall, this initiative positively contributed to the empowerment of coastal women through skill enhancement and economic independence based on local potential, while also supporting the achievement of Sustainable Development Goals (SDGs) related to poverty alleviation and economic growth. Abstrak. Wilayah pesisir Provinsi Banten memiliki potensi besar dalam sektor perikanan, terutama di Desa Domas, Kabupaten Serang, yang dikenal sebagai penghasil ikan Payus. Namun, keterbatasan inovasi dalam pengolahan hasil tangkapan menyebabkan nilai jual ikan masih rendah, sementara sebagian besar keluarga nelayan bergantung sepenuhnya pada hasil laut yang tidak menentu akibat faktor cuaca. Melihat kondisi tersebut, Mahasiswa Himpunan Mahasiswa Logistik Kelautan (HIMALOKA) Universitas Pendidikan Indonesia melaksanakan kegiatan pengabdian kepada masyarakat yang bertujuan untuk meningkatkan keterampilan kewirausahaan dan kemandirian ekonomi istri nelayan. Melalui pelatihan pengolahan ikan Payus menjadi produk Crispy Bontot (CRISBON), peserta diperkenalkan pada proses inovasi produk, teknik pengemasan yang menarik, serta strategi pemasaran digital untuk memperluas jangkauan pasar. Kegiatan ini menggunakan pendekatan Participatory Action Research (PAR) yang melibatkan masyarakat secara aktif mulai dari tahap perencanaan hingga evaluasi. Hasil pelaksanaan menunjukkan adanya peningkatan kemampuan peserta pada aspek kewirausahaan, inovasi produk, kemasan, dan pemasaran digital. Peningkatan tertinggi dicapai pada kemampuan pemasaran digital sebesar 12,18%, menunjukkan bahwa peserta mulai mampu memanfaatkan teknologi sebagai sarana promosi dan pengembangan usaha. Secara keseluruhan, kegiatan ini berkontribusi positif terhadap pemberdayaan perempuan pesisir melalui peningkatan keterampilan dan kemandirian ekonomi berbasis potensi lokal, sekaligus mendukung pencapaian Tujuan Pembangunan Berkelanjutan (SDGs) mengenai pengentasan kemiskinan dan pertumbuhan ekonomi.